CC-010 Laying on of the healing hands. (23rd September 2015) - Sweis, R; Anggiansah, A; Forgacs, I; Wong, T; Fox, M
Abstract : Introduction: Rumination Syndrome is common yet under-diagnosed and is becoming increasingly recognised in healthy individuals. The primary feature is regurgitation occurring 5–10 min after initiating a meal. It is often confused with disorders such as gastro-oesophageal reflux disease, and patients may be subject to extensive yet unnecessary investigations. Treatment effectiveness with acid reducing medications and prokinetics is limited. The most favourable outcome is achieved with Diaphragmatic Breathing exercises. This case presentation describes the journey of a patient who was found to have rumination syndrome following high-resolution manometry (HRM) and was treated successfully with Diaphragmatic Breathing. Methods: HRM (Manoscan 360°, SSI) with 10×5 ml water and 5×1 cm 3 solid (bread) swallows and a 250 ml milkshake was performed in the in the upright seated position. This was followed by dual channel 24-h catheter-based pH monitoring. Treatment encompassed two sessions of diaphragmatic therapy. Results: HRM: During the bread swallows and after drinking the milkshake, typical symptoms of regurgitation were reproduced. These were associated with short, sharp increases in the intragastric pressure sensors typical of Rumination Syndrome. 24-h Ambulatory reflux study: This exhibited a normal measurement for frequency of reflux events and a positive Symptom Index (87.1%; positive greater than or equal to 50%) for regurgitation. Conclusion: Although in this example it was discovered with the use of HRM in a tertiary centre, Rumination Syndrome should be easily diagnosed based only on clinical history. This condition is usually treated with diaphragmatic breathing techniques, however patient commitment to therapy and perseverance is paramount. Diaphragmatic breathing is thought to overwhelm the subconscious yet voluntary abdominal wall muscle contractions which lead to regurgitation, and was successful in this case.